Dosis dan Waktu Pemberian Pupuk KCl terhadap Pertumbuhan dan Hasil Jagung Manis - Shodiq Eko Ariyanto; Suharijanto Suharijanto; Khairul Anwar; Asung Damar Sanubari (Agrotechnology Research Journal, 2024)
This study aimed to determine the optimal dose and time of KCl fertilizer application that can increase the growth and yield of sweet corn (Zea mays var. saccharata). The study was conducted on land owned by the Secondary Crop Seedling Development Plantation Rendole I Pati from July to October 2022. The method used,  was a factorial experiment with a completely randomized block design consisting of two factors, each having three replications. The first factor is the dose of KCl fertilizer (d), which consists of four levels). The first factor is the dose of KCl fertilizer (d) consisting of four levels, namely 0, 50, 100, and 150 kg ha-1. The second factor is the time of KCl fertilizer application (p), namely: administration at 15 and 30 days after planting (p1) and administration at 15 and 45 days after planting (p2). The results showed that the dose of KCl fertilizer affected various parameters of growth and yield of sweet corn plants, between fresh cob cloth with and without husks, fresh weight of cobs, cob length, cob diameter, number of seeds per row, and sugar content. The dose of 100 kg ha-1 showed better results, especially in increasing the fresh weight of cobs with husks and the weight of cobs. Meanwhile, the time of KCl fertilizer application only affected the height of sweet corn plants at the age of 5 days after planting. There was no significant interaction between the dose of KCl fertilizer and the time of KCl fertilizer application. Therefore, to increase the yield of sweet corn, it is recommended to use a dose of KCl fertilizer of 100 kg ha-1 and apply it at the ages of 15 and 30 days after planting.